2018
DOI: 10.1002/adbi.201800039
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Terbium into a Microalga Leads to Magnetotactic Swimmers

Abstract: Swimming microorganisms have been shown to be useful for the propulsion of microrobotic devices due to their self-powered motion. Up to now, mainly bacteria, e.g., magnetotactic bacteria (MTB), are investigated as biohybrid microrobots. But biocompatibility studies of MTB regarding medical utilizations are still lacking. Moreover, MTB require special culture conditions for their stability, which also might limit their usage for biomedical applications. Herein, a cytocompatible, highly motile microswimmer is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 58 publications
0
35
0
Order By: Relevance
“…Of particular interest are magnetotactic bacteria, which can readily be steered by applying magnetic fields [7,8]. Organisms that are not naturally magnetotactic can also be controlled with magnetic fields after incorporation of magnetic particles; this has recently been demonstrated with the alga Chlamydomonas reinhardtii [9]. Commonly studied magnetotactic bacteria include the strains MO-1 and MC-1 ( Magnetococcus marinus ), which are similar in morphology and differ from the species most widely studied in other contexts, such as Escherichia coli , Bacillus subtilis , or Vibrio alginolyticus .…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest are magnetotactic bacteria, which can readily be steered by applying magnetic fields [7,8]. Organisms that are not naturally magnetotactic can also be controlled with magnetic fields after incorporation of magnetic particles; this has recently been demonstrated with the alga Chlamydomonas reinhardtii [9]. Commonly studied magnetotactic bacteria include the strains MO-1 and MC-1 ( Magnetococcus marinus ), which are similar in morphology and differ from the species most widely studied in other contexts, such as Escherichia coli , Bacillus subtilis , or Vibrio alginolyticus .…”
Section: Introductionmentioning
confidence: 99%
“…Different lanthanides accumulate in different parts of the cells 32. We also showed that the microalgae species Chlamydomonas reinhardtii , which does not produce coccoliths, takes up Tb 3+ and accumulates them as nanoparticles inside the cells 33. The accumulation of lanthanides in coccoliths were not investigated so far.…”
Section: Introductionmentioning
confidence: 94%
“…An approach to provide magnetic properties to the microalga species C. reinhardtii is to culture them in a media containing terbium ions (Tb 3 + ). [ 237 ] These ions are known to possess magnetic properties and to present photoluminescence and could therefore potentially be used as a biomarker. The grown microalgae presented superparamagnetic properties and their motion could be controlled by magnetic fields and tracked by their photoluminescence.…”
Section: Magnetic Biohybrid Cellular Micro‐biorobotsmentioning
confidence: 99%